Post-Earthquake Community Service at SDN Sarampad, Cianjur: The Needs of Existence, Relatedness, Growth (ERG) for Elementary School’s Students and Teachers - Liza Agustina Maureen Nelloh; Leonnard Ong; Yulita Susanti; Sony Wiwiek Antonio; Sidrotun Naim; Sasotya Pratama (Sekolah Tinggi Manajemen IPMI, 2023)
earthquake has shaken the earth of Cianjur and has given a lot of pain and trauma to the citizen in many sectors, including education, especially for elementary schools. As planned, the PAS (final exam assessment) would be held simultaneously from December 5 to December 9, 2022. However, the big earthquake at the end of November, has devastated the dreams of every schools in Cugenang, Cianjur to follow the PAS. Cugenang regency got the significant impact on destruction of school buildings and houses. Elementary schools have lost their opportunity to follow the PAS on time and stopped giving the education service since then. Therefore, Directorate General of Higher Education, Research and TechnologyMinistry of Education, Culture, Research and Technology (Kemenristekdikti) has given the opportunity for some higher education institutions to help Cianjur. SDN Sarampad in Cugenang Region, Cianjur has stopped their education activities since the earthquake because the limitation of living and damage caused of the school buildings. They lost the needs of ERG (existence, relatedness, growth) and have no plan for the PAS anymore. Hence, STM IPMI planned for the ERG Program to students class 1, 2, 3, 4, 5, 6 to SDN Sarampad from the earliest December to the latest December 2022. In total there were three visits to SDN Sarampad to support their ERG needs and preparing the students and teachers to continue the educational activities.